A Study of Student Counselors' Experiences With Meditation. Issue 2 (7th October 2019) - Gutierrez, Daniel; Merrill, Erica; Conley, Abigail H.; Young, Mark E.
Abstract : The positive effects of meditation have been shown to be helpful to a variety of client populations and counselors in practice. Researchers analyzed the journals of 60 counselor education students who volunteered to learn Jyoti meditation (JM) over a 6‐week period. Analysis revealed 5 major themes: (a) the scheduling of time for meditation, (b) issues with concentrating, (c) environment for meditation, (d) effects on wellness, and (e) adherence to daily practice. These themes suggest avenues for how counselor educators and supervisors can help student counselors integrate JM as a self‐care strategy.